2015
DOI: 10.1073/pnas.1507508112
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of lithium polyhydrides above 130 GPa at 300 K

Abstract: The prediction of novel lithium hydrides with nontraditional stoichiometries at high pressure has been seminal for highlighting a promising line of research on hydrogen-dense materials. Here, we report the evidences of the disproportionation of LiH above 130 GPa to form lithium hydrides containing H 2 units. Measurements have been performed using the nonperturbing technique of synchrotron infrared absorption. The observed vibron frequencies match the predictions for LiH 2 and LiH 6 . These polyhydrides remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 25 publications
7
46
0
Order By: Relevance
“…The observed Raman shifts are plotted as a function of pressure in Fig. (a) together with the previously reported results for Raman active modes of LiH, the Raman vibrons [ Q 1( J ) Raman ] of pure H 2 , the IR absorbance measurement of LiH n , and the most intense calculated phonon of LiH 2 . It can be found that the pressure dependence of the Raman shift of ‘bulk H 2 ’ indicated by the closed square in Fig.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…The observed Raman shifts are plotted as a function of pressure in Fig. (a) together with the previously reported results for Raman active modes of LiH, the Raman vibrons [ Q 1( J ) Raman ] of pure H 2 , the IR absorbance measurement of LiH n , and the most intense calculated phonon of LiH 2 . It can be found that the pressure dependence of the Raman shift of ‘bulk H 2 ’ indicated by the closed square in Fig.…”
Section: Resultssupporting
confidence: 52%
“…Pressure dependences of Raman shifts for the ν1–ν9 (a) and the full width at the half height of ‘bulk H 2 ’ and Q 1( J ) Raman of pure H 2 (b). In (a), the Raman vibrons [ Q 1( J ) Raman ] of pure H 2 , Raman active modes of LiH, the calculated phonon of LiH 2 , the IR absorption peak wavenumber for LiH n , and the calculated vibron of the elongated H 2 in CsH 7 , BaH 6 , and RbH 5 are plotted together . [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel polyhydrides predicted theoretically to become stable at high pressure [2,3] are good candidates to realize such expectations but several experimental efforts were inconclusive [4][5][6]. Recently, however, following the theoretical prediction [3], superconductivity up to 203 K in the H-S system at above 144 GPa has been reported [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, numerous theoretical studies have been performed that investigate the phase diagrams of hydrogen doped with the electropositive alkali metals or alkaline earth metals [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], as well as the electronegative element iodine [35,36] under pressure. Experimental work on the hydrides of lithium and sodium confirmed that species with unique stoichiometries such as NaH 3 and NaH 7 can be synthesized in diamond anvil cells, but the phases that have been reported to date do not exhibit superconductivity [21,37]. Nonetheless, as summarized in this short review, the aforementioned theoretical explorations have: revealed that rich structural variety may be found in the hydrogenic sublattices, suggested a number of ways that hydrogen may be metalized via doping, and shown that the propensity for superconductivity is linked to the nature of the hydrogenic motifs.…”
Section: Introductionmentioning
confidence: 99%